Impact of Glutamine-Enhanced Parenteral Nutrition on Postoperative Outcomes in Colorectal Cancer Patients - Huang Y; Yin C; Wang J; Wang M; Zheng X; Xie M; Wang J (Cancer Management and Research, 2024)
Yong Huang,* Chunmei Yin,* Jue Wang, Maijian Wang, Xingbin Zheng, Ming Xie, Jiwei Wang Department of General Surgery, Digestive Disease Hospital, Affiliated Hospital of Zunyi Medical University, Zunyi, Guizhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jiwei Wang, Department of General Surgery, Digestive Disease Hospital, Affiliated Hospital of Zunyi Medical University, 149 Dalian Road, Huichuan District, Zunyi, Guizhou, People’s Republic of China, Tel +86-13017410630, Email wjw@smail.nju.edu.cnPurpose: This study investigated the effects of parenteral glutamine (Gln) supplement immunonutrition versus conventional nutritional support on postoperative Clavien–Dindo classification complications and recovery, perioperative nutritional status, and immune, inflammation, and safety indicators in patients with colorectal cancer (CRC).Patients and Methods: Clinical data were collected for a retrospective cohort study of 178 patients (58 and 120 patients in the observation and control groups, respectively) who underwent radical resection of CRC from January 2019 to December 2021. The incidence of postoperative complications was calculated. Postoperative recovery, nutritional indicators, inflammatory factors indicator, and the safety indicators before operation and at 1, 3, and 7 days after operation were compared. SPSS 29.0 statistical software was used for statistical analysis.Results: The incidence of postoperative overall complications in the control group and the observation group was 22.50% (27/120) and 17.24% (10/58), respectively, and there was no significant difference between the two groups (P=0.42). The incidence of postoperative complications of Clavien-Dindo grade ≥III in the control group and the observation group was 14.17% (17/120) and 3.45% (2/58), respectively, and the difference between the two groups was statistically significant (P=0.03). Secondary outcomes (first exhaust, defecation, and liquid diet intake times) were significantly recovered earlier in the observation group than those in the control group (P< 0.05), while the postoperative hospital stay was significantly shorter(P=0.04). The perioperative nutritional status did not significantly differ between the groups before and after surgery(P> 0.05), although significant differences were observed in several inflammatory and safety indicators(P< 0.05).Conclusion: Unlike conventional nutritional support, postoperative parenteral Gln supplementation reduced the incidence of postoperative Clavien–Dindo complications grade ≥III in patients with CRC while increasing intestinal and immune functions, decreasing inflammation, and reducing the length of hospital stay.Keywords: glutamine, parenteral nutrition, colorectal cancer, clavien–dindo complication